2013
DOI: 10.1039/c3ob40162f
|View full text |Cite
|
Sign up to set email alerts
|

Staphyloferrin A as siderophore-component in fluoroquinolone-based Trojan horse antibiotics

Abstract: A series of fluoroquinolone conjugates was synthesised by linking the carboxylic acid functionality of the carboxylate-type siderophore staphyloferrin A and its derivatives to the piperazinyl nitrogen of ciprofloxacin and norfloxacin via amide bond formation. Four siderophore-drug conjugates were screened against a panel of bacteria associated with infection in humans. Whilst no activity was found against ciprofloxacin- or norfloxacin-resistant bacteria, one of the conjugates retained antibacterial activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 22 publications
1
57
0
4
Order By: Relevance
“…The hydrophilicity nature of staphyloferrin A improves the water solubility of its conjugates and enhances the rate of transport of the drug to the cell (Milner et al 2013). Since Staphylococcus aureus secretes staphyloferrin siderophores, Milner et al synthesized a series of novel staphyloferrin based Trojan horse conjugates and tested the antimicrobial properties of those conjugates on Staphylococcus aureus (Milner et al 2013). It was reported that one of the conjugate was found to exhibit antimicrobial property against Staphylococcus aureus (Milner et al 2013).…”
Section: Trojan Horse Antibioticsmentioning
confidence: 98%
See 4 more Smart Citations
“…The hydrophilicity nature of staphyloferrin A improves the water solubility of its conjugates and enhances the rate of transport of the drug to the cell (Milner et al 2013). Since Staphylococcus aureus secretes staphyloferrin siderophores, Milner et al synthesized a series of novel staphyloferrin based Trojan horse conjugates and tested the antimicrobial properties of those conjugates on Staphylococcus aureus (Milner et al 2013). It was reported that one of the conjugate was found to exhibit antimicrobial property against Staphylococcus aureus (Milner et al 2013).…”
Section: Trojan Horse Antibioticsmentioning
confidence: 98%
“…Since Staphylococcus aureus secretes staphyloferrin siderophores, Milner et al synthesized a series of novel staphyloferrin based Trojan horse conjugates and tested the antimicrobial properties of those conjugates on Staphylococcus aureus (Milner et al 2013). It was reported that one of the conjugate was found to exhibit antimicrobial property against Staphylococcus aureus (Milner et al 2013). Staphylococcus aureus can colonize human skin and gut and associates with some problematic health-care-associated infections, including surgical site infections, bacteraemias, and lower respiratory tract infections (Milner et al 2013).…”
Section: Trojan Horse Antibioticsmentioning
confidence: 98%
See 3 more Smart Citations